Evaluasi Sistem Elhamzah Shafira Tour And Travel Cabang Jember Menggunakan COBIT 4.1 - Ardina Sagita Ramadhani Ardina; Firdaus Akmal Fauzan (Universitas Mercu Buana Yogyakarta, 2023)
The Elhamzah system is a system used by all Shafira Tour and Travel branches, including Shafira Tour and Travel Jember Branch. So far, the system evaluation process has only been carried out at the Shafira Tour and Travel Center, while the other branches have never carried out system evaluation and assessment. Therefore, this study was conducted to evaluate and assess the Elhamzah system in Shafira Tour and Travel Jember Branch. In the process of evaluating and assessing this system, we use the COBIT 4.1 framework with the Monitor and Evaluate domain. The results we get are the ME1 gap of 0.36, ME2 of 0.56, ME3 of 0.50, and ME4 of 0.38.